2007
DOI: 10.1108/00483480710716759
|View full text |Cite
|
Sign up to set email alerts
|

The impact of culture on Chinese employees' work values

Abstract: PurposeThe purpose of this article is to investigate the detailed relationships between Chinese cultural values (Confucian dynamism, individualism, masculinity, and power distance) and work values (self‐enhancement, contribution to society, rewards and stability, openness to change, and power and status) in an integrated model. Further attempts are also made to explain the above relationship in terms of different cultural exposure experiences.Design/methodology/approachThe sample was collected from China (sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 28 publications
1
73
1
Order By: Relevance
“…Nevertheless, an inherent limitation involved with this present study, was that the Confucian Dynamism measure used in this study might not be completely valid. Although other researchers have also used this scale, its reliabilities have not been reported (Ralston et al 1992;Robertson and Hoffman 2000;Robertson 2000;Jaw et al 2007). In this study, the reliabilities (Cronbach's alpha) were not especially high.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Nevertheless, an inherent limitation involved with this present study, was that the Confucian Dynamism measure used in this study might not be completely valid. Although other researchers have also used this scale, its reliabilities have not been reported (Ralston et al 1992;Robertson and Hoffman 2000;Robertson 2000;Jaw et al 2007). In this study, the reliabilities (Cronbach's alpha) were not especially high.…”
Section: Discussioncontrasting
confidence: 46%
“…In addition, Lu et al (1999) found individuals high in Confucian Dynamism are also more likely to place greater importance on other stakeholders than themselves. Moreover, Jaw et al (2007) noted that respondents with high Confucian Dynamism tend to emphasize self-enhancement, contribution to society, stability and rewards, and openness to change simultaneously. It was also found that such individuals are more likely to confine themselves within social norms (Lu et al 1999;Ornatowski 1996).…”
Section: Confucian Dynamismmentioning
confidence: 97%
“…Valentine (2000) states the relevance of person-job fit, person-organisation fit, and cultural differences in determining recruitment success. Studies have revealed that culture is a differentiating factor between work values (Hofstede 1980;Pelled and Xin 1997;Schneider and Barsoux 1997;Trompenaars and Hampden-Turner 1998;Holden 2002;Jaw et al 2007). Indians, being members of relationship-oriented vertical culture may project different work values than western culture.…”
Section: Introductionmentioning
confidence: 96%
“…These cultural values have significantly influenced the Chinese way of life and personality (Wah, 2002). Confucianism also has found to foster self-enhancement and work values of Chinese employees (Jaw, Ling, Wang and Chang, 2007).…”
Section: Chinese Business Performancementioning
confidence: 99%